Effects of Different Rates of Nitrogen Fertilisation and Biological Preparations to Increase Nitrogen Use Efficiency on Yield Structure Elements in Maize - Vytautas Liakas; Aušra Marcinkevičienė; Aušra Rudinskienė; Vaida Steponavičienė (Agronomy)
The soil used for the field experiment was PLb-g4 Endohipogleyic Eutric Planasol. The research aimed to investigate the effects of different nitrogen fertilisation rates and biological preparations on yield structure elements and partial factor productivity of nitrogen in maize (Zea mays L.) grown for grain production. The factors studied were Factor A—nitrogen (N) fertiliser rates: (1) 100 kg ha−1, (2) 140 kg ha−1, and (3) 180 kg ha−1, and Factor B—use of biofertilisers: (1) no biological preparations (BP) used, (2) biological preparation (AB)—nitrogen bacteria Paenibacillus polymyxa (1.0 L ha−1), (3) biological preparations (AB + C)—nitrogen bacteria Paenibacillus polymyxa (1.0 L ha−1) and cytokinin, and (4) biological preparations (AB + H)—nitrogen bacteria Paenibacillus polymyxa (1.0 L ha−1) and humic acids. The research showed that the yield of maize grain was significantly increased not only by increasing the rates of nitrogen fertilisation but also by using biological preparations. The highest maize grain yield (11.5 t ha−1) was obtained in 2020 using N180 fertilisation, in combination with biological preparations AB + H. In all cases, the biological preparations and their combinations significantly increased the maize grain yield compared to the control field (no use of BP). The biological preparations in combination with N significantly increased the weight of 1000 grains and thus the grain yield per plant. The highest maize grain yield per plant (154.6 g) was obtained in 2020 using N180 fertilisation, in combination with biological preparations AB + H. In most cases, positive, strong, very strong, and statistically significant correlations were observed between the different rates of nitrogen fertilisation and the indicators studied: r = 0.76–0.94 (p < 0.01, p < 0.05). No statistically significant correlation was found between nitrogen fertilisation rates and the number of grains per cob (p > 0.05). The highest partial factor productivity of nitrogen fertiliser (92.0 kg of maize kg−1 of N) was obtained in 2020 using N100 fertilisation, in combination with AB + H. Increasing the nitrogen fertiliser rates and not using biological preparations resulted in a decrease in the partial factor productivity of nitrogen fertiliser.